IMPLEMENTING DMG MODEL TO IMPROVE RELIABILITY OF PERSONAL COMPUTER AT COMPUTER LABORATORY FACILITY - Emon Azriadi; Aris Fiatno (Jurnal Teknik Industri Terintegrasi, 2018)
A typical maintenance organisation has responsibility in keeping the production facility running at the desired level performance. In order to ensure that condition, necessary decisions should be made. The Decision Making Grid (DMG) model is one of analysis technique that provides maintenance organisation in strategic and tactical level management to determine the appropriate maintenance policy for all individual machinery and equipment within the facility. In this project, the analysis identified the performance of the personel computer at laboratory facility by conducting availability measurement. The hardware, peripheral, and softwarewhich have breakdown records were analysed then by the DMG model to propose the appropriate maintenance policy for all individual personel computer within the computer laboratory facility. Implementing the DMG recommendations were proposed to follow the suggested priority order.